2006
DOI: 10.1093/qjmam/hbl002
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastohydrodynamic drag on a particle moving near a deformable wall

Abstract: Naire, Shailesh, and Oliver E. Jensen. Epithelial cell deformation during surfactant-mediated airway reopening: a theoretical model. J Appl Physiol 99: 458 -471, 2005. First published March 31, 2005 doi:10.1152/japplphysiol.00796.2004.-A theoretical model is presented describing the reopening by an advancing air bubble of an initially liquid-filled collapsed airway lined with deformable epithelial cells. The model integrates descriptions of flow-structure interaction (accounting for nonlinear deformation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 65 publications
4
27
1
Order By: Relevance
“…Both led to an evolution equation that is integro-differential in form, which reflects the fact that linearized unsteady Stokes flow, present in the lubrication region, has long been known to possess memory effects (Boussinesq 1885;Basset 1888). In the absence of inertia, the integro-differential equation was seen to reduce down to the linearized form of the well-known partial differential equation that governs the quasi-steady regime (Lighthill 1968;Weekley et al 2006;Balmforth et al 2010), as expected.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Both led to an evolution equation that is integro-differential in form, which reflects the fact that linearized unsteady Stokes flow, present in the lubrication region, has long been known to possess memory effects (Boussinesq 1885;Basset 1888). In the absence of inertia, the integro-differential equation was seen to reduce down to the linearized form of the well-known partial differential equation that governs the quasi-steady regime (Lighthill 1968;Weekley et al 2006;Balmforth et al 2010), as expected.…”
Section: Discussionsupporting
confidence: 62%
“…(Of course, convective inertia is also negligible in this inner region, since the nonlinear terms are now multiplied by D 2 Re 1.) Whereas earlier studies (Lighthill 1968;Weekley et al 2006) considered the regime where unsteady inertia is unimportant (a → ∞), table 1 suggests that we find ourselves in the novel regime where a ∼ 1 (i.e. If the body's surface in the lubrication region (II) is designated as lying at z = −s 1 (x) when stationary, we note that the body shape can be represented locally as a power series expansion about x = 0, i.e.…”
Section: Formulationmentioning
confidence: 83%
“…However, Weekley et al (2006), who considered the approach of a parabolic surface towards a flat surface coated with a thin elastic layer through a thin layer of Newtonian fluid, found that the elastic layer deforms in such a way as to create a fluid layer of approximately uniform thickness, with the consequence that the approach is qualitatively the same as that of two flat rigid surfaces. Since the femoral condyles are roughly parabolic and cartilage is poroelastic, we anticipate qualitatively similar behaviour in the knee, and thus modelling the femoral condyles as a flat bearing is not an unreasonable first model.…”
Section: Conclusion and Application To The Human Knee Jointmentioning
confidence: 99%
“…The motion of an object close to a wall with intervening fluid is one of the cornerstones of lubrication studies, where an established finding is the growth in lift generated on the object upon approach, enabling the design of robust and effective bearing setups [2][3][4]. Furthermore, there is rich literature on 'soft lubrication' too, where either the approaching object or the wall or both are deformable [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], which finds applications in topics ranging from biotransport modelling [25][26][27][28] to tool design and analysis [29][30][31]. Such soft-lubrication setups are wide-spread in both natural and man-made world, examples being scanning probe microscope (SPM) and surface force apparatus (SFA) setups [32][33][34][35][36][37][38][39][40][41] and motion of biological entities like red blood corpuscles (RBCs) in fluidic environments [42][43][44].…”
Section: Introductionmentioning
confidence: 99%